Murder book : a graphic memoir of a true crime obsession - Campbell, Hilary Fitzgerald (Andrews McMeel Publishing, 2021)
"Why is it so much fun to read about death and dismemberment? In Murder Book, lifelong true-crime obsessive and New Yorker cartoonist Hilary Fitzgerald Campbell tries to puzzle out the answer. An unconventional graphic exploration of a lifetime of Ann Rule super-fandom, amateur armchair sleuthing, and a deep dive into the high-profile murders that have fascinated the author for decades, this is a funny, thoughtful, and highly personal blend of memoir, cultural criticism, and true crime with a focus on the often-overlooked victims of notorious killers."